Managing Consumer Confusion in Online Tourism: The Impact of AI on Decision Postponement ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Tourism companies are available online with abundant choices which lead to consumer’s confusion.  Objective: The study aims to understand and analyse the impact of consumer confusion leading to decision  postponement with role of artificial influence using stimulus organism response [SOR] model. Methodology: Mixed  method research with both qualitative and quantitative approach has been performed and analysis is carried out using  SPSS 27 for factor analysis and Smart PLS 4 for measurement and path analysis. A total of 284 self-filled questionnaire  responses were used for examining the consumer confusion. Results: Through stimulus organism response model; the  antecedents, consequences, mediators, moderators and the application of constructs in various contexts have been  reported. A framework along with the questions and scope for the future research has been proposed. Conclusion: The  study enlightened on how AI lead travel sites and websites offer similar packages to the consumers with minimal to no  differences driving to confusion, creating difficulty in adapting the destination choice which in turn leads to decision  postponement. This study provides insightful information and awareness for travel/tourism companies, tourists and  academicians on how confusion affects decision making.
Keywords: Consumer confusion; decision postponement; artificial intelligence; destination choice; information and communication technology